Cultural Influences on Ethnopsychiatry Nursing Practices: A Systematic Review of Key Factors Shaping Cross-Cultural Mental Health Care - Fatma Lutfiyatus Sayyida; Indi Dwi Shofi Yanti; Anggun Novia Indah Fitri (Tarqabin Nusantara Group, 2025)
Ethnopsychiatry nursing is increasingly recognized as a critical component of mental health care in multicultural societies. This systematic review explores the key cultural factors that influence psychiatric nursing practices, drawing on evidence from 25 peer-reviewed studies published between 2010 and 2025. Guided by a multidisciplinary framework integrating Leininger’s Culturally Congruent Care Theory, Campinha-Bacote’s Process of Cultural Competence Model, and Kleinman’s Explanatory Model of Illness, the study identifies six core cultural dimensions: cultural competence and awareness, social and family structures, communication and language barriers, ethnocentrism and cultural imposition, structural and systemic adaptations, and integration of traditional healing practices. Findings reveal that culturally competent care significantly enhances therapeutic relationships, diagnostic accuracy, and treatment adherence. Nurses who engage in continuous intercultural training demonstrate greater empathy, reduce biases, and foster inclusive environments. Family and community involvement, particularly in collectivist cultures, plays a pivotal role in emotional support and treatment compliance. Language barriers remain a persistent challenge, highlighting the necessity of professional interpreters and cultural brokers to facilitate meaningful communication. Ethnocentric attitudes among healthcare providers were found to hinder effective care delivery, underscoring the need for institutional strategies promoting cultural humility. Systemic adaptations within healthcare organizations, including policy reforms and culturally tailored assessment tools, are essential for equitable service provision. The integration of traditional healing practices further strengthens patient trust and engagement, particularly in communities where holistic or spiritual approaches are predominant. In conclusion, this review affirms that cultural competence is not an optional aspect of psychiatric nursing but a foundational requirement for delivering effective, respectful, and patient-centered mental health care. Recommendations include enhancing nurse education, implementing supportive policies, and fostering collaborative models that respect and incorporate cultural diversity in clinical practice.understanding and responding to the diverse cultural contexts in which mental health care is practiced.